A Clinical Evaluation Of The Performance Of 3 Resin Based Composites In Posterior Restortion-An Invivo Study - Singh, Tarun Kumar; Choudhary, Ekta; Gill, Ikroop; Modgi, Chetan (Journal of Neonatal Surgery, 2025)
The aim of this study was to evaluate the performance of 3 different composites: Packable, Microhybrid and Nanohybrid as a posterior restorative material in class 1 carious lesion. The purpose was to evaluate and compare the clinical behaviour under the following criterias : Color match, Cavosurface marginal discoloration, Secondary caries, Anatomic form (wear), Marginal adaptation and Post operative sensitivity. 60 class 1 lesions were restored , 20 each with packable composite, microhybrid composite and nanohybrid composite. Patients with class 1 carious lesions in permanent molars were selected. The assessment were done according to USPHS criteria. It was then concluded that all materials showed satisfactory results as far as retention was concerned. But the marginal integrity and appearance of Filtek TM Z350 was better.